Content generated by users, operation and benchmarking in hostels In São Paulo - Yamauchi, Eryck Yudi Tomita; Oliveira, Rodrigo Ribeiro de; Zatta, Fernando Nascimento (Brazilian Journal of Production Engineering, 2022)
Being one of the main tourist destinations in Brazil, São Paulo receives many tourists of different categories and objectives. A style of travel that is becoming popular in São Paulo and in the world is Low Cost, and so low-cost establishments such as hostels are also increasingly in evidence. The planning and control of production operations and guest service are essential for organizations that seek success in business, so that the elaboration of activities results in guest satisfaction, cost reduction, resource optimization, production time , control of the efficiency of the results and alteration of the project, when necessary. Thus, this work aimed to identify, analyze and describe what are the planning and control practices existing in Hostels in the city of São Paulo in order to verify the efficiency with which such establishments perform their services.
Keywords: Tourism; hostel; operations planning; São Paulo; benchmarking